Peran dan Tantangan Kecerdasan Buatan (AI) dalam Pendidikan Tinggi: Implementasi dan Implikasi Etis - Kasman, Risqah Amaliah; Burhan; Abdul Munir HB (Almeera Education, 2025)
This study aims to analyze the impact and challenges of implementing artificial intelligence (AI) in education in Indonesia. The method used is a literature study with a descriptive qualitative approach, which involves the systematic collection and analysis of literature from academic journals in the last three years. The results of the study indicate that AI contributes significantly to improving learning personalization, administrative efficiency, and automated evaluation. However, there are challenges such as data privacy risks, student over-reliance, technology gaps, and algorithm bias. Therefore, regulations, increased digital literacy, and development of technological infrastructure are needed to ensure ethical and inclusive implementation of AI in education.